Importance of accurately locating the entry site for endovascular treatment of retrograde Type A acute aortic dissection. (2nd January 2018) - Urbanski, Paul P; Sodah, Ayman; Matveeva, Anna; Irimie, Vadim; Wagner, Matthias; Agaev, Arzou; Schmitt, Rainer
Abstract: OBJECTIVES: The aim of this study was to evaluate the diagnostic possibilities of accurately locating the entry site in acute retrograde Type A aortic dissection and the results of the corresponding endovascular treatments. METHODS: Among 100 patients who underwent surgery for the treatment of spontaneous acute Type A aortic dissection between 2012 and June 2017, all but 1 patient had preoperative computed tomographic angiography. A total of 8 retrograde extensions originated from the descending aorta, in which 6 of them were diagnosed correctly using radiological imaging. The surgical team was unable to properly diagnose the entry site using radiological imaging in only 1 patient, and no preoperative computed tomographic-angiographic scans were available for 1 other patient. In the latter case, the retrograde dissection was diagnosed intraoperatively and confirmed by postoperative computed tomographic angiography. RESULTS: In 5 patients, a tear-oriented endovascular repair was performed based on preoperative radiological findings. In the remaining 3 patients, conventional surgery of the proximal aorta was performed because of the clinical situation (e.g. aortic insufficiency, pericardial effusion) and/or diagnostic uncertainty. One patient subsequently underwent an endograft successfully. All patients survived surgery and were alive at the last follow-up; however, complete remodelling of the thoracic aorta was evident in only patients with endovascular repair. CONCLUSIONS: Tear-oriented endovascular repair of acute Type A aortic dissection originating from the descending aorta seems to be a valuable and durable therapeutic option. However, the determination of the entry site in the descending aorta is a prerequisite for this type of treatment. Therefore, the surgical team should consider a diagnostics based on modern, sophisticated radiological methods.